Protective effects of curcumin against aflatoxicosis: A comprehensive review. Issue 4 (14th November 2017) - Mohajeri, Mohammad; Behnam, Behzad; Cicero, Arrigo F. G.; Sahebkar, Amirhossein
Abstract : Aflatoxicosis is a deleterious medical condition that results from aflatoxins (AFs) or ochratoxins (OTs). Contamination with these toxins exerts detrimental effects on the liver, kidneys, reproductive organs, and also on immunological and cardiovascular systems. Aflatoxicosis is closely associated with overproduction of reactive oxygen species (ROS) as key contributors to oxidative and nitrosative stress responses, and subsequent damages to lipids, proteins, RNA, and DNA. The main target organ for AF toxicity is the liver, where DNA adducts, degranulation of endoplasmic reticulum, increased hepatic lipid peroxide, GSH depletion, mitochondrial dysfunction, and reduction of enzymatic and non‐enzymatic antioxidants are manifestations of aflatoxicosis. Curcuma longa L. (turmeric) is a medicinal plant widely utilized all over the world for culinary and phytomedical purposes. Considering the antioxidant characteristic of curcumin, the main active component of turmeric, this review is intended to critically summarize the available evidence supporting possible effectiveness of curcumin against aflatoxicosis. Curcumin can serve as a promising candidate for attenuation of the adverse consequences of aflatoxicosis, acting mainly through intrinsic antioxidant effects aroused from its structure, modulation of the immune system as reflected by interleukin‐1β and transforming growth factor‐β, and interfering with AF's biotransformation by cytochrome P450 isoenzymes CYP1A, CYP3A, CYP2A, CYP2B, and CYP2C. Abstract : Aflatoxicosis is a deleterious medical condition that results from aflatoxins (AFs) or ochratoxins (OTs). Aflatoxicosis is closely associated with overproduction of reactive oxygen species (ROS) as key contributors to oxidative and nitrosative stress responses, and subsequent damages to lipids, proteins, RNA, and DNA. Curcumin can serve as a promising candidate for attenuation of the adverse consequences of aflatoxicosis, acting mainly through intrinsic antioxidant effects aroused from its structure, modulation of the immune system as reflected by interleukins, and interfering with AF's biotransformation by cytochrome P450 isoenzymes.